Effects of Different Pressure Levels in Topical Negative Pressure Application-Analysis of Perfusion Parameters in a Clinical Skin Model Using Multimodal Imaging Techniques - Aslan-Horch, Emine Ceylan; Horch, Raymund E.; Arkudas, Andreas; Müller-Seubert, Wibke; Ludolph, Ingo (Journal of Clinical Medicine, 2022)
The effects of topical negative pressure therapy (TNP) have been a subject of research for many years. In this study, we investigated new imaging devices to detect clinical changes that TNP causes on healthy tissue and identified differences in microcirculation created by different pressure levels. We used near-infrared spectroscopy (NIS), thermography, and a vein illuminator to measure the differences in oxygen saturation, tissue temperature, and vein pattern. A control group (-125 mmHg) and three comparison groups with only TNP dressing (Group 1), -25 mmHg (Group 2), and -175 mmHg (Group 3) were established. Thirty minutes of TNP on intact skin was followed by 30 min of resting. A total of 24 participants were measured by all imaging devices at predetermined time points. Oxygen saturation and skin temperature increased by 8.07% and 1.67 degrees C for the control group, 4.00% and 1.65 degrees C for Group 2, and 8.45% and 1.68 degrees C for Group 3. Group 1 showed a slight increase in oxygen saturation and a 2.7 degrees C increase in skin temperature. Over the 30 min following removal of TNP, oxygen saturation and temperature decreased gradually for all groups. The vein illuminator did not show significant differences in the venous pattern or flow. Our study showed that higher negative pressure values resulted in higher oxygen saturation and higher tissue temperature.
CRIS-Team WoS Importer:2022-09-16